Numerical simulation of pollutant dispersion in urban roadway tunnels. (March 2017) - Dong, Jingliang; Tao, Yao; Xiao, Yimin; Tu, Jiyuan
Vehicular toxic emissions can easily contaminate the air quality of the enclosed tunnel environment, especially during rush hours with traffic jam events or low vehicle speeds, which poses serious health hazards to road utilizers. The piston effect generated by moving vehicles was normally considered adequate to discharge vitiated air out of short tunnel based on a typical driving speed. However, complex traffic conditions may yield unexpected consequences on in-tunnel air quality levels. This study numerically investigated the CO2 concentration to identify the in-tunnel pollutant dispersion under three traffic conditions including severe traffic congestion and traffic flow with low vehicle speeds. Fan conditions were considered to model the influence of mechanical winds on pollutant dispersion and comparison with vehicular piston effect was also performed. The results revealed elevated pollutant concentration regions were found at the vicinity of near-ground region and tunnel downstream. The vehicular piston effect can sufficiently remove the in-tunnel vehicular emissions when vehicles travel at relatively higher speed. However, pollutant accumulation occurs when vehicles are idling or moving at slow speed. Compared with traffic piston effect at high travelling speed, the mechanical ventilation of ceiling mounted fans only generate a limited contribution to the removal of emissions.